(untitled) (Journal of Society of Surgeons of Nepal, 2023)
Introduction: Neoadjuvant chemoradiation (NACRT) may result in significant response in rectal cancer. Conventional imaging may not be accurate. 18FDG-PET/CT scan has shown promising results for monitoring the response to NACRT. The aim of this study is to evaluate the role of 18FDG-PET/CT scan in predicting pathological response after NACRT in carcinoma rectum. Methods: Thirty-two consecutive patients with locally advanced rectal cancer were enrolled. Patients underwent NACRT comprising of external beam radiotherapy and concomitant infusional 5-FU based chemotherapy. It was followed 6 weeks later by total mesorectal excision. All patients underwent FDG-PET/CT before and minimum 6 weeks after the completion of NACRT. Maximum standardized uptake (SUVmax) value was calculated. The tumor regression grade (TRG) in resected specimen was scored according to the Mandard criteria. TRG 1-2 was considered as responders and TRG 3-5, non-responders. The SUVmax within the tumor was correlated to differentiate pathological responders from non-responders. Results: Fourteen of 30 patients were excluded due to protocol deviation. Following NACRT, 7 (50%) patients were classified as responders (TRG 1-2) and 7 (50%) non-responders (TRG 3-5). There were no significant differences in pre NACRT SUVmax between responders (12.05±2.81) and non-responders (17.65±7.20) (p=0.079). The mean post-NACRT SUVmax was significantly lower in responders than non-responders (6.4 vs 10.8; p=0.024). To compare the response using ROC curve analysis (AUC=0.83), and considering a cut-off post SUVmax as 7.0, the sensitivity was 57.14%, specificity 71.43%, positive predictive value (PPV) 66.67%, negative predictive value (NPV) 62.50%, and the overall accuracy was 64.28% to differentiate pathological responders from non-responders. Conclusion: These preliminary results suggest that 18FDG-PET/CT could be a potentially useful tool in predicting response after NACRT in locally advanced rectal cancer. Post SUVmax of 7.0 appears to be the best predictor tumor response following NACRT.